2012
DOI: 10.1016/j.econlet.2011.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Returns to education in professional football

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We should note that over the considered period, mean and median salaries increased monotonically; however, the lack of control for this increase in real salaries does not affect our analyses because this monotonic increase is already captured while controlling for season-specific unobservable characteristics. We should also note that draft age (similar to age at school entry for studies on the RAE in education) is affected by players’ relative age, as suggested in past research [ 38 , 39 , 40 ]. This inclusion as a control variable improves our interpretation of the RAE estimates, as has been adopted in studies on salary discrimination based on ethnicity where performance measures have been analyzed (for a literature review see [ 41 ]).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…We should note that over the considered period, mean and median salaries increased monotonically; however, the lack of control for this increase in real salaries does not affect our analyses because this monotonic increase is already captured while controlling for season-specific unobservable characteristics. We should also note that draft age (similar to age at school entry for studies on the RAE in education) is affected by players’ relative age, as suggested in past research [ 38 , 39 , 40 ]. This inclusion as a control variable improves our interpretation of the RAE estimates, as has been adopted in studies on salary discrimination based on ethnicity where performance measures have been analyzed (for a literature review see [ 41 ]).…”
Section: Methodsmentioning
confidence: 93%
“…To offset the inherent unfairness of the RAE and the later RAE reversal on performances, understanding these mediating factors could be used to better select talent and encourage resiliency of players. Although previous literature on the RAE in sports and education [ 38 , 39 , 40 ] suggests delaying entry into professional sports/school to reduce performance gaps, the reversal complicates this view as there are potential benefits of being the “underdog.” Finally, from the perspective of the RAE in term of representativeness, our results suggest that adjustments of the drafting rules could reduce the disadvantages suffered by relatively young players.…”
Section: Discussionmentioning
confidence: 99%
“…The relative age effect (RAE) refers to the possible advantage that children get when being relatively old in their cohort, that is, children born early in the calendar year perform better that those born later. The existence of an RAE in various professional sports and educational performance is well documented (see, e.g., Musch and Grondin, 2001, Bedard and Duhey, 2006, Böheim and Lackner, 2012, Fredriksson and Öckert, 2014, and Fumarco and Rossi, 2018. The academic and policy interest here arises for four primary reasons.…”
Section: Introductionmentioning
confidence: 99%
“…To test the research hypothesis that age of entry has an effect on NFL career, I adopted the following multiple dependent variables, as there is no consensus measure of NFL career success: 6 weighted career approximate value (CARAV) 7 , length of NFL career in years (CRYR) 8 , years as primary starter (YRPS), and all-pro selection (APS). Dependent variables were modeled 1 Entry age is calculated as the difference between the year of draft and the year of birth to eliminate variation that is caused by the seasonality of hiring (Böheim & Lackner, 2012 Rosen, 2006). 7 For a full description regarding the calculation of CARAV, see Pro-Football-Reference.com.…”
Section: Data and Analytical Frameworkmentioning
confidence: 99%
“…Specific to the NFL, playing careers have been investigated vis-à-vis returns to college education (Böheim & Lackner, 2012), the influence of off-field conduct (Stair, Day, Mizak, & Neral, 2008), round of draft pick (Hendricks, Debrock, & Koenker, 2003), and managerial life cycle (Goff & Wisley, 2006). Such emerging research has consistently pointed out that labor supply in the NFL is determined by one's natural talents, attitude toward risk and precocity.…”
Section: Introductionmentioning
confidence: 99%